Adverse reactions to food additives: the extent and severity of the problem. Food, brain and behaviour. Conference proceedings October 1996, Allergy Research Foundation. - Millstone E (Journal of Nutritional & Environmental Medicine)
A comprehensive review is provided of published studies purporting to cast light on the frequency of the occurrence of acute adverse reactions to food additives among children. The strengths and weaknesses of those studies are discussed and the review concludes that most of the published estimates understate the true scale of the problem and that the overall incidence among British children is unlikely to be below 1% or above 20%. The policy implications of those findings are set out.